Randomized Controlled Trial of the Effect of 30% versus 80% Fraction of Inspired Oxygen on Cesarean Delivery Surgical Site Infection - Williams, Ned L.; Glover, Melanie M.; Crisp, Catrina; Acton, Angus L.; Mckenna, David S. (American Journal of Perinatology, 2013)
Objective To determine if supplemental perioperative oxygen will reduce surgical site infection (SSI) following cesarean delivery.Methods This is a randomized, controlled trial evaluating SSI following either 30% or 80% fraction of inspired oxygen (Fio2) during and 2 hours after cesarean delivery. Anesthesia providers administered Fio2 via a high-flow oxygen blender. Subjects, surgeons, and wound evaluation teams were blinded. Serial wound evaluations were performed. Data were analyzed using logistic regression models, Fisher exact test, and t test.Results In all, 179 women were randomized, and 160 subjects were included in the analysis. There were 12/83 (14.5%) SSIs in the control group versus 10/77 (13.0%) in the investigational group (p = 0.82). Caucasian race, increased body mass index, and longer operative time were identified as significant risk factors for infection (p = 0.026, odds ratio 0.283; p = 0.05, odds ratio = 1.058; p = 0.037, odds ratio = 1.038, respectively).Conclusion Perioperative oxygenation with 80% Fio2 is not effective in reducing SSI following cesarean delivery.
Keywords: cesarean; Fio2; infection; surgical; oxygen